Participatory research with youth with disabilities: Experiences from sub-Saharan Africa - Bannink Mbazzi, Femke; Hameed, Shaffa; Ganle, John K; Shakespeare, Tom; Polack, Sarah (African Online Scientific Information Systems (Pty) Ltd t/a AOSIS, 2024)
Background: Disability inclusive youth research, involving youth with disabilities in the design, implementation and dissemination of study data, is still limited in Africa.Objectives: To describe and reflect on the experiences of involving youth with disabilities in an exploratory research study, focused on disability-inclusive education and employment in 7 African countries.Method: 12 youths with different impairments, aged 18 to 35, were employed as researchers in Ethiopia, Ghana, Kenya, Nigeria, Rwanda, Senegal and Uganda. Youth researchers contributed to the data collection and analysis of interviews with 210 youth with disabilities. 24 youth advisors with disabilities formed two youth advisory groups (YAG) of 12 advisors each in the regional hub countries Ghana and Uganda. The YAGs met 4 times during the project and contributed to the study design, data collection, data analysis and dissemination activities. In addition, 4 workshops were held with the Ugandan YAG to develop a participatory film.Results: Together with the youth participants, we reflected on the experiences of involving youth with disabilities and conducting research with, by and on youth with disabilities. We highlighted ethics and safeguarding, recruitment and representation, exploring experiences and data quality, participatory dissemination, accessibility, capacity building and networking as key areas of consideration and benefit in this project.Conclusion: Participatory research with youth with disabilities is feasible, enriching, and key to inclusive research that informs education and employment policy and practices.Contribution: Lessons learned from youth involvement in a disability inclusive research programme, focused on education and employment in 7 African countries.